Efecto de cinco aceites vegetales en el crecimiento, composición bromatológica, variación de los parámetros hematológicos: glucosa, colesterol, trigliceridos y hematocrito en alevinos de “gamitana” Colossoma macropomum (Cuvier, 1818) - Guzmán Cáceres, Rosa Andrea (2017)
Lipids are important sources of energy and essential fatty acids and play an important role in the metabolism of fat-soluble vitamins, which can significantly affect the quality of the meat product produced by the industry. The purpose of the research was to evaluate the effects of the dietary inclusion of five vegetable oils (soybean, palm, sunflower, corn and sacha inchi) on the growth, bromatological composition and variation of hematological parameters of gamitana fingerlings, Colossoma macropomum. We carried out the tests at the "Fernando Alcántara Bocanegra" Research Center of the IIAP Quistococha. One hundred and five fingerlings of 1,5 g and 5 cm of initial weight and length, respectively, were randomly distributed in 15 fiberglass troughs. The fish were fed their respective diets twice daily using a 5% feeding rate for 60 days. Every 10 days the biometric growth of the fish was recorded, while the bromatological analyzes were carried out at the beginning and at the end of the trial. Water quality was evaluated daily (pH, dissolved oxygen, and temperature) and biweekly (alkalinity, total hardness, ammonium, nitrite, and carbon dioxide), using a multiparameter and a freshwater analysis kit. Hematological analysis was carried out at the end of the study. The growth values and bromatological analysis of the fingerlings did not show significant differences (P>0,05) between the diets, with the exception of hematocrit and hemoglobin. The water quality remained within the appropriate ranges for "gamitana". Due to their low costs and wide availability in the market, soybean and palm oils should be mainly used in the formulation and preparation of diets for the fingerling phase of this fish.